The Percentage of Trees Bearing Cones as a Predictor for Annual Longleaf Pine Cone Production - Thomas Patterson (Frontiers in Forests and Global Change, 2021)
The U.S. Forest Service has monitored longleaf pine cone production at sites throughout the southeastern United States for over 60 years. Data from the multi-decadal surveys have supported our understanding of the variability of stand-level cone production as it relates to environmental and ecological processes, and more broadly, how longleaf pine operates as a masting species. Cones from longleaf pine are counted each spring using visual surveys that follow a standard protocol. Rapid mast assessments have been proposed in the literature as an alternative to traditional methods, yet these approaches have not been examined for longleaf pine. In this study, I compared average cone production (using the traditional method) to the percentage of trees bearing cones (rapid assessment) to understand the relationship between these two mast measurements. I examined 29 years of data from 18 cone-monitoring sites containing 234 trees. Using simple linear models, I discovered the percentage of trees bearing cones explained 58–94% of the variance in log-average cone production across all sites. One-way ANOVA analysis revealed cone crops required for successful regeneration (25 + cones per tree) occurred when the percentage of trees bearing cones exceeded 90%, and the results from this study underscore the utility of a simple 90% threshold when determining a successful cone crop. While traditional cone-count methods should not be abandoned, I advocate for the use of rapid cone-crop assessments when a proxy approach is suitable.